Towards the use of distance sampling to monitorize mountain ungulates numbers. - Perez, J.M. (2012)
Many management actions involving mountain ungulates require unbiased and precise estimations of their numbers. Topography, among other factors, makes difficult the use of direct methods and to assess the effective area sampled. On the other hand, social behaviour of animals increases the risk to violate the assumption that observations must be independent events. This could be avoided using the group or cluster size as a covariate and estimating density of animals through the density of clusters. In this paper we revise the increasing potential of Distance Sampling methodology to estimate mountain ungulate populations. We address different problems which compromise some of the assumptions and discuss several topics concerning the importance of assessing effective area sampled, estimation of g(0), and model selection when attempting to adapt the use of Distance Sampling to a three-dimensional scenarios, like mountainous habitats and ungulate populations.